2018
DOI: 10.1038/gim.2017.151
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of publicly available LDLR, APOB, and PCSK9 variants associated with familial hypercholesterolemia: application of ACMG guidelines and implications for familial hypercholesterolemia diagnosis

Abstract: PurposeFamilial hypercholesterolemia (FH) is an autosomal disorder of lipid metabolism presenting with increased cardiovascular risk. Although more than 1,700 variants have been associated with FH, the great majority have not been functionally proved to affect the low-density lipoprotein receptor cycle. We aimed to classify all described variants associated with FH and to establish the proportion of variants that lack evidence to support their pathogenicity.MethodsWe followed American College of Medical Geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 39 publications
2
72
1
4
Order By: Relevance
“…In the Portuguese FH Study only if a variant is classified as pathogenic or likely pathogenic (ACMG), or if the variant is designated as a VUS, only after functional in vitro assessment with proof of affected function, the clinician is informed that the variant found confirms or is consistent with the clinical diagnosis. Due to the establishment of functional studies in our lab, the majority of the mutations found in the Portuguese population (120/142) have a classification of pathogenic or likely pathogenic following ACMG guidelines, and this results in more than 80% of our cohort of FH/M+ patients having a molecularly confirmed FH diagnosis. The implementation of functional studies as an adjunct to work in diagnostic laboratories improves the genetic diagnosis of FH, and should be encouraged worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Portuguese FH Study only if a variant is classified as pathogenic or likely pathogenic (ACMG), or if the variant is designated as a VUS, only after functional in vitro assessment with proof of affected function, the clinician is informed that the variant found confirms or is consistent with the clinical diagnosis. Due to the establishment of functional studies in our lab, the majority of the mutations found in the Portuguese population (120/142) have a classification of pathogenic or likely pathogenic following ACMG guidelines, and this results in more than 80% of our cohort of FH/M+ patients having a molecularly confirmed FH diagnosis. The implementation of functional studies as an adjunct to work in diagnostic laboratories improves the genetic diagnosis of FH, and should be encouraged worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…22 All variants were checked with Mutalyzer 2.0, as recommended by HGVS. Variants were classified as pathogenic, likely pathogenic, variant of uncertain significance (VUS), likely benign or benign, according to the American College of Medical Genetics and Genomics (ACMG) guidelines 23 following specific adaptations described in Chora et al 24 The variants reported in the present study were considered novel if they were not described before in public databases 25,26 or in PUBMED, and novel for Portugal if they were found for the first time in Portugal, but have been previously reported in another country. In silico analysis was performed as described before.…”
Section: Monogenic Dyslipidaemia Analysismentioning
confidence: 99%
“…NICE guidelines [17] also advocate that only relatives of genetically positive index cases should be offered genetic testing to establish mutation positive FH. The obvious downside is that with over 1700 known FH mutations [48], not all are amenable to genetic testing and up to 40% may be missed [9].…”
Section: 222mentioning
confidence: 99%
“…As principais alterações no LDLR são as mutações na extremidade 5'UTR (0,8%), pequenas deleções (1,6%), grandes rearranjos cromossômicos (9,0%), mutações sem sentindo (nonsense, 9,0%), mutações por deslocamento (frameshift, 18,0%), mutações na região de processamento de RNA (splicing, 9,0%) e mutação de sentido trocado (missense, 46,0%) (CHORA et al, 2018;MARDUEL et al, 2010).…”
Section: Mais De 2000 Mutações Já Foram Descritas Neste Gene Segundounclassified
“…Avaliar a relação das diferentes variantes encontradas por ultrassequenciamento em pacientes com HF é de grande importância para compreender os mecanismos pelos quais as variações genéticas influenciam na concentração de colesterol e consequentemente o processo patológico desta doença (FORTI et al, 2003;SILVA et al, 2012). Recentemente um grupo identificou que apenas cerca de 8% das variantes no LDLR identificadas no banco de dados ClinVar são completamente caracterizadas por estudos in vitro (CHORA et al, 2018).…”
Section: Com O Avanço Dos Estudos De Associação Do Genoma Completo (Gunclassified